Incidence of infection in carpal tunnel surgery with and without the use of local antibiotics - Bilal Khan; Alam, Ikram; Ullah, Sajjad; Jamal, Bakht (Journal of the Pakistan Medical Association, 2023)
Objective: To compare the infection rate in patients who underwent carpal tunnel surgery with and without instilling local antibiotics into the surgical wound. Method: The retrospective cohort study was conducted at the Department of Surgery, Unit of Neurosurgery, Government Naseer Ullah Babar Memorial Hospital, Peshawar, Pakistan, and comprised data from July 2019 to July 2021 related to non-diabetic patients without any comorbidity who had undergone fresh carpal tunnel surgery. The cases had been operated by two surgeons having a different approach to preventing infection in carpal tunnel surgery cases. The surgeon in group A did not use any local antibiotics after completing the surgery, while the surgeon in group B instilled local gentamicin in the open wound for 3 minutes after completing the nerve release. All patients were put on oral antibiotics for a period of 5 days after the procedure in both the cohorts, and were assessed fortnightly for any infection and removal of stitches. Demographics of the patients, use of antibiotics and the occurrence of infection were recorded on a proforma. Data was analysed using SPSS 20. Results: Of the 177 patients operated during the period, 13(7.3%) was discarded owing to missing data. Of the 164(92.7%) patients analysed, 138(84.14%) were females and 26(15.85%) were males. The overall mean age was 32.46±8.97 years. The total surgeries conducted were 176; 96(54.54%) in group A and 80(45.45%) in group B. Infections were found in 3(1.7%) patients; all in group A (p=0.160). Conclusion: Although not statistically significant, instillation of local antibiotics may play a role in preventing surgical site infections in carpal tunnel surgery cases. Key Words: Topical antibiotics, Local antibiotics, Carpal tunnel surgery, Gentamicin, Infection.